Penerapan Sistem Manajemen Lingkungan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRAK This research aims to analyze the influence of the implementation of EMS ISO 14001 at PT. Semen Padang to the quality change of dust emission and dust ambient before a the implementation at FT, Semen Padang. Three sample areas were taken purposively based on the wind direction and speed. These sample areas are named WI, TTG3, and TBLS. Data acquesitions were carried out using checklist on ISO 14001 element, questionaire on the management of ISO 14001, measurement of ambient air quality on each sample area using High Volume Air Sampler (HVAS) method. The collected data were statistically analysed to evaluate whether significant difference occurs between the quality of air emission and ambient before and after the implementation of EMS ISO 14001. Descriptive analysis were employed in the respect. The result of this research indicates that the implementation of EMS LSO 14001 at Semen Padang influences the quality of dust emission significantly. For the dust emission, however, the significant influence does not exist. The implementation of EMS T50 14001 at PT Semen Padang are effective and efficient enough. Anyhow, some elements arc not effectively and effeciently Kata kunci: Environmental